Flood vulnerability of the town of Tanay, Rizal, Philippines - Pati, Romeo C.; Cruz, Amabel P. (2017)
Flood and social vulnerability analyses were used to assess the dynamics and social impact of flood in the flood plains of Tanay. Flood simulation was carried out using the derived hydrograph as input in the simulation model. The social vulnerability of each of the flood-prone barangays in the town was also determined using proxy indices such as strength of public infrastructure, demographic and socio-economic factors. The model successfully predicted the flood depths and delineated the spatial extent of flooding in the different barangays of the town. This was shown by the simulated flood depths that were comparable with the observed flood depths of the communities in seven out of nine flood-prone communities in Tanay. Barangay Tabing Ilog had the highest overall vulnerability index, indicating that this barangay is the most vulnerable to flood and needs a comprehensive flood risk preparedness and social development plan to increase the coping capacity of the residents to flooding. (Author's abstract)
Includes bibliographical references (pages 115-116)
Keywords: Social sciences; Flood simulation; flood vulnerability; GIS mapping; Socio-economic index; Social vulnerability; Storm hydrograph